Factors Influencing Continuance Intention of GoFood Healthy Food Customers - Maishita, Chandra Bella; Abas, Novel Idris (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aims to explore the effect of e-service quality, perceived healthfulness of food, and packaging quality on customer satisfaction, as well as the direct effect of price on continuance intention on GoFood. Methodology: This study uses a quantitative approach by collecting data from 255 GoFood user respondents in Indonesia. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the relationship between variables. Results: The results show that e-service quality, perceived healthfulness of food, and packaging quality significantly affect customer satisfaction, which in turn affects continuance intention. In addition, price was found to have a significant direct effect on continuance intention. Applications/Originality/Value: This study provides a novel contribution in the context of healthy food delivery services, particularly by highlighting the important role of price as a direct predictor of continuance intention. The practical implications of this study indicate that service providers such as GoFood should improve their service and packaging quality and implement effective pricing strategies to retain customers.